Exploratory data analysis to reveal learning loss condition in Islamic religious education - Rohmat Mulyana; Dian Sa'adillah Maylawati (Institute of Advanced Engineering and Science, 2024)
One of the negative impacts of this prolonged distance teaching and learning activity during the pandemic is that students lag in absorbing lessons, known as learning loss. Islamic religious education (IRE) as value education, especially in Indonesia, can also cause learning loss. This study aims to identify possible indications of learning loss experienced by madrasa students in IRE. This study uses data science methods with an exploratory data analysis (EDA) approach. Respondents are students in the sixth grade of Madrasah Ibtidaiyah (MI), the ninth grade of Madrasah Tsanawiyah (MTs), and the twelfth grade of Madrasah Aliyah (MA). The total respondents in this study were 38,326 MI students, 29,350 MTs students, and 13,474 MA students. The results of the EDA found that most madrasas in Indonesia experienced indications of learning loss in IRE subjects during distance learning during the COVID-19 pandemic, both at the MI, MTS, and MA levels. This study found that the learning loss condition is influenced by various states and readiness for distance learning, both the preparedness of students to learn independently, the availability of digital content that is interesting and easy to understand, as well as the availability of facilities and technology for distance learning.